Historical Studies Of Japan During The Meiji Restoration - Anita, Anita; Tadu Lado, Sisilia Helena Joaline (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
This research aims to find out the history of Japan during the Meiji Restoration. The research method used in this research is the historical method, because the object of this research aims to describe and analyze past events. The results of the research are that the Meiji Restoration had an impact on changes in various areas of life in Japanese society. Meiji restoration means recovery, which includes development and renewal. In this case, the restoration of power is both theoretical and practical. The Meiji restoration carried out by Meiji Tenno covered the political sector, the economic sector, the educational sector and the military sector. Long before the Meiji restoration, Japan was considered a weak, backward country and prey to Western imperialist countries. However, after restoration in all areas it turned out to produce truly amazing results. The progress that Japan experienced in various fields after the Meiji Restoration not only made the Japanese people prosperous, but also became a developed nation that was competitive with Western countries.